Assessing children's proficiency in a minority language: exploring the relationships between home language exposure, test performance and teacher and parent ratings of school-age Irish-English bilinguals. (4th July 2019) - Nic Fhlannchadha, Siobhán; Hickey, Tina M.
ABSTRACT: There can be significant diversity in the language experience of minority language children, and in the levels of proficiency reached. The declining numbers of children now exposed to Irish include those from homes where only/mainly Irish is spoken, those with only one Irish-speaking parent, and children from homes where one/both parent(s) speak 'some Irish', while levels of language use in the wider community also vary widely. The proficiency of children from Irish-speaking homes seems impressive compared with their L2 learner classmates, but still shows particular linguistic needs. Since acquisition of complex morphosyntactic features depends on both the quantity and quality of input, and extends well into the school years, assessing children's performance on features such as grammatical gender may provide a useful index of need for language enrichment, even among young speakers judged by teachers and parents to be fluent. We report data from 306 Irish-speaking participants aged 6–13 years from a range of language backgrounds, most of whom live in Gaeltacht (officially designated Irish-speaking) areas. Information was collected from parents on children's home language and new measures of receptive and productive use of grammatical gender marking in Irish were administered. Performance on these measures is compared with scores on standardised measures of Irish and English reading vocabulary, as well as teacher and parent ratings.